Supercontinuum Generation in Photonic Crystal Fibers Infiltrated with Liquids - Van, Cao Long (Communications in Physics, 2021)
In this paper we present the development of a new direction in so-called optofluidics , namely the research of photonic crystal fibers (PCF) infiltrated with liquids. In particular we concentrate on the flagship application of PCF, the process of Supercontinuum Generation (SG), in which injected monochromatic pulse may be dramatically broadened (spectrally), which creates a coherent beam generation of high brightness comparable to that of monochromatic lasers. The supercontinuum is formed when a collection of nonlinear processes act together upon a pump beam in order to cause severe spectral broadening of the original pump beam. Explanation of this process is based on numerical simulations for Generalized Nonlinear Schrödinger equation (GNLSE) which describes the rich nonlinear dynamics of pulse propagation in nonlinear dispersive media. All nonlinear phenomena involved in SG will be analyzed. We present specially activity of the Polish-Vietnamese Group from the beginning in 2016 to recent time in this domain.